Formation of cognitive independence of students using Google services - T. B. Shustakova (Academy of Cognitive and Natural Sciences, 2017)
Research goals: determine the impact of Google services on forming cognitive independence of students. Research objectives: analysis of existing methods of forming cognitive independence of students, analysis of Google services in education, the place and role of Google services on formation of cognitive independence of students, identify learning tool using Google services for the formation of cognitive independence of students. Object of research: forming cognitive independence of students in school I-III stages. Subject of research: use Google services for the formation of cognitive independence of students. Research methods used: analysis of scientific publications and personal experience. Results of the research. Based on psychological and pedagogical literature analyzed existing approaches to the formation of cognitive independence of students using the services of Google. The place and role of Google services on formation of cognitive independence of seniors. Defined learning tool using Google services for the formation of cognitive independence of students. The main conclusions and recommendations. Use the Google services forming cognitive independence high school students is appropriate and promising development in modern pedagogical practice.